Semilattices global valuations in the topos approach to quantum mechanics - Freytes Solari, Hector Carlos (2017)
In the framework of the topos approach to quantum mechanics a kind of global valuation is introduced and studied. It allows us to represent certain features related to the logical consequences of properties about quantum systems when its phase space is endowed with an intuitionistic structure